Pertumbuhan Kompensasi dan Efisiensi Produksi Ayam Broiler yang Mendapat Pembatasan Waktu Makan - A Azis; H Abbas; Y Heryandi; E Kusnadi (Faculty of Animal Science, Bogor Agricultural University, 2011)
The present study was designed to investigate the effect of feeding time restriction on compensatory growth and production efficiency of broiler chickens. Four hundred of 7 days-old unsexed broiler chicken of Lohmann commercial strain were used in the experiment. The treatments were: bird fed ad libitum as a control treatment (R-0); bird had free access to feed during two periods of 2 hours (08:00-10:00 and 16:00-18:00) from 7-14 days of age (R-1) and 7-21 days of age (R-2); bird had free access to feed during two periods of 4 hours (08:00-12:00 and 16:00-20:00) from 7-14 days of age (R-3) and 7-21 days of age (R-4). The treatments were arranged in a completely randomized design with 4 replications. Feed intake and body weight gain of chicken exposed to feeding time restriction on R-1, R-2, R-3 and R-4 were lower (P < 0.01) than those of chicken fed ad libitum. There were no significant different on feed intake and body weight gain during realimentation period. Compensatory growth occured on R-2 and R-4 during the 28 to 42 days of age and similar body weight with control at age 42 days. Feed conversion ratio on R-2 and R-4 were lower (P < 0.01) feeding time restriction (7-21 days) and realimentation period (28-35 days). It was concluded that feeding time restriction for 8 hours per day from 7 to 21 days of age indicated compensatory growth and similar body weight and had better feed cost and production index than that of control.